Comparison of tasselled cap components of images from Landsat 5 Thematic Mapper and Landsat 7 Enhanced Thematic Mapper Plus. Issue 2 (2nd July 2016) - Liu, Qingsheng; Liu, Gaohuan; Huang, Chong; Xie, Chuanjie; Chu, Lin; Shi, Lei
Abstract: Use of the tasselled cap transformation (TCT) is widely accepted in the remote sensing community, but there is concern whether the TCT components from each unique tasselled-cap-like feature space from different sensors are directly comparable. This study compared the differences of the TCT components from Landsat 5 Thematic Mapper (TM) and Landsat 7 Enhanced TM Plus (ETM+) images with different TCT coefficients from paired images. The results demonstrated that time series analysis of Landsat images using the TCT components derived from Landsat 5 TM and Landsat 7 ETM+ digital numbers (DNs) or at-satellite reflectance could introduce errors. Through converting Landsat 5 TM to Landsat 7 ETM+ DNs prior to the TCT transformation, the RMSEs were reduced by >62 percent. Overall, it was better to derive the TCT components from at-satellite reflectance images, normalised by relative radiometric correction, based on the TCT coefficients for Landsat 7 ETM+ at-satellite reflectance.